Global correlation of the early Cambrian of South Australia:shelly fauna of the Dailyatia odyssei Zone - Betts, Marissa J.; Paterson, John R.; Jago, James B.; Jacquet, Sarah M.; Skovsted, Christian B.; Topper, Timothy P.; Brock, Glenn A. (Gondwana Research, 2017)
A lack of well resolved biostratigraphic data has prevented robust regional and global correlation of lower Cambrian successions from South Australia. A new early Cambrian biostratigraphy, based on data derived from 21 measured stratigraphic sections and drill cores (11 described herein) reveals the abundance and diversity of shelly fauna from the Arrowie Basin, and the value of early Cambrian “small shelly fossils” (SSF) for biostratigraphic studies. Here we examine shelly fauna associated with the youngest of three recently established biozones, the Dailyatia odyssei Taxon Range Zone (hereafter D. odyssei Zone), and their correlative potential. The D. odyssei Zone features a diverse suite of tommotiids, organophosphatic brachiopods, bradoriid arthropods, molluscs and phosphatic problematica. This fauna permits strong correlation (often at species-level) with other major early Cambrian terranes, particularly Antarctica, South China and Laurentia, and suggest a Cambrian Series 2, Stages 3–4 age for the D. odyssei Zone. Bradoriids have proven to be useful biostratigraphic tools. Four new species and three new genera are described herein: Acutobalteus sinuosus gen. et sp. nov., Eozhexiella adnyamathanha gen. et sp. nov., Manawarra jonesi gen. et sp. nov. and Mongolitubulus descensus sp. nov. The description of Eohadrotreta sp. cf. zhenbaensis represents the first occurrence of the acrotretoid brachiopod Eohadrotreta from Australia.